2019
DOI: 10.1128/jvi.00047-19
|View full text |Cite
|
Sign up to set email alerts
|

The Transcriptome of Latent Human Cytomegalovirus

Abstract: The latent human cytomegalovirus (HCMV) transcriptome has been extremely difficult to define due to the scarcity of naturally latent cells and the complexity of available models. The genomic era offers many approaches to transcriptome profiling that hold great potential for elucidating this challenging issue. The results from two recent studies applying different transcriptomic methodologies and analyses of both experimental and natural samples challenge the dogma of a restricted latency-associated transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…Finally, late genes are expressed after viral DNA replication has commenced and encode mostly structural proteins of the capsid, tegument or envelope required for the assembly and egress of progeny virions [19][20][21]. HCMV replicates in a wide variety of differentiated cell types, and targets select types of poorly differentiated cells including myeloid progenitors for latent infection with limited viral gene expression [22][23][24][25][26]. Viral reactivation from latency is brought about by cellular differentiation and/or stimulation and contributes greatly to pathogenesis in vulnerable hosts [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, late genes are expressed after viral DNA replication has commenced and encode mostly structural proteins of the capsid, tegument or envelope required for the assembly and egress of progeny virions [19][20][21]. HCMV replicates in a wide variety of differentiated cell types, and targets select types of poorly differentiated cells including myeloid progenitors for latent infection with limited viral gene expression [22][23][24][25][26]. Viral reactivation from latency is brought about by cellular differentiation and/or stimulation and contributes greatly to pathogenesis in vulnerable hosts [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…HCMV can establish lytic or latent infection in different cell lines (Schwartz and Stern-Ginossar, 2019). THP-1 macrophages are usually used as an HCMV experimental lytic infection model (Sanchez et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of viral gene expression have taken advantage of the development of sensitive, high throughput, and unbiased analyses to interrogate the latent viral transcriptome in both naturally and experimentally infected myeloid cells (Rossetto et al, 2013;Cheng et al, 2017;Shnayder et al, 2018;Schwartz and Stern-Ginossar, 2019). In contrast to earlier reports, these studies detected expression of many lytic genes, and did not find evidence for a latency-specific transcriptional profile.…”
Section: Latency: Are There Latency-specific Transcripts?mentioning
confidence: 93%
“…Single cell analysis of experimentally infected monocytes has shed some light on this paradox (Shnayder et al, 2018(Shnayder et al, , 2020Schwartz and Stern-Ginossar, 2019). This study revealed that there is marked heterogeneity in the cellular response to infection.…”
Section: Latency: Are There Latency-specific Transcripts?mentioning
confidence: 98%